Clinicopathological and molecular analyses of uterine carcinosarcomas using next-generation sequencing: A single-center experience - Ezgi Genç Erdoğan; Tülin D. Yalta; Nuray Can; Necdet Süt; Ebru Taştekin; Ufuk Usta; Fulya Öz Puyan; Fatma E. Usturalı Keskin; Busem B. Kurt (Indian Journal of Pathology and Microbiology)
Background: Uterine carcinosarcomas (UCS) constitute 3–4% of all uterine malignancies and 16% of deaths caused due to uterine neoplasms. Aim: In this study, we aimed to perform DNA-based mutation analysis in 12 genes (KRAS, NRAS, EGFR, C-KIT, BRAF, PDGFRA, ALK, ERBB2, ERBB3, ESR1, RAF1, PIK3CA) to determine the molecular subtypes of UCS using next-generation sequencing (NGS) in patients with aggressive UCS and poor prognosis. We aimed to compare the results of our analysis with clinicopathological data to contribute to the development of targeted therapy approaches related to the molecular changes of UCS. Materials and Methods: In this study, we included 12 cases diagnosed with uterine carcinosarcomas and examined the changes in oncogenes that play a role in UCS pathogenesis. For the analysis of mutation, the clinicopathological data were compared with the variations in the DNA-based gene panel consisting of 12 genes and 1237 variants in the UCS using the NGS method. Results: EGFR mutation was found in 91.7% of the cases, mutation in 41.7%, PDGFRA mutation in 25%, KRAS and PIK3CA mutation in 16.7%, and C-KIT mutation in 8.3% of the cases. Although no statistical significance was found between the detected mutation and clinicopathological data, it was concluded that PDGFRA mutation might be associated with advanced-stage disease development. Conclusion: This study's findings regarding different molecular types of UCS and information on oncogenesis of UCS can provide inferences for targeted therapies in the future by identifying targetable mutations representing early oncogenic events and thereby contribute toward further studies on this subject.